THE BINGO GAME AND ITS INFLUENCE ON THE LISTENING SKILL IN ENGLISH LANGUAGE IN THE STUDENTS OF THE NINTH GRADE OF BASIC EDUCATION, "HERIBERTO RODRÍGUEZ ANGULO" EDUCATIONAL UNIT EL CARMEN-MANABÍ 2017-2018 ACADEMIC PERIOD. - VIVAS INTRIAGO, INÉS BEATRIZ (2018)
THE GAME OF BINGO IS THE DEVELOPMENT OF THE ABILITY TO LISTEN, IT IS ONE OF THE MAIN FACTORS OF SUCCESS IN THE PROCESS OF ACQUIRING OR LEARNING A FOREING LANGUAGE GENERALLY, IT IS DEVELOPED THROUGH EXERCISES AND ACTIVITIES TEACHER OR STUDENT, ADDITIONALLY, THE CURRENT TRENDS IN LISTENING HAVE INCORPORATED THE MANAGEMENT OF NEW MECHANISMS TO STRENGTHEN TEACHING-LEARNING, ESPECIALLY IN FOREIGN LANGUAGE TEACHING...